Análise de dependência espacial da taxa de mortalidade por Covid-19 nos municípios brasileiros - Vítor Hugo Campelo Pereira; Glairton Cardoso Rocha; Marco Túlio Mendonça Diniz; Marcos Antonio Cavalcante de Oliveira Júnior (Confins)
This article aims to analyze the distribution of deaths by COVID-19 in Brazilian municipalities and its relationship with socioeconomic aspects (income) until the data of July 14, 2020. A methodology was based on the selection of spatial autocorrelation based on the Global Index Moran and the Local Moran Index (LISA) in its univariate and bivariate forms. A univariate form was used to investigate the distribution of the Mortality Rate by COVID-19 (CMD), while the bivariate form was used to verify spatial autocorrelation between the variables TMC (dependent variable) and MHDI Income (independent variable) in Brazilian municipalities until the data of July 14, 2020. The results show the presence of clusters formed from groups of municipalities with high CMD values, mainly in the North and Northeast regions of Brazil. In addition, a negative autocorrelation was found between the variables TMC and MHDI Income, with emphasis on large territorial portions of the North and Northeast regions. The number of cases of COVID-19 in a geographical area and the income of its population are essential factors for understanding the distribution of habits related to this disease.